Effect of Y element on cyclic stability of A2B7 -type La–Y–Ni-based hydrogen storage alloy. (13th August 2019) - Liu, Yuru; Yuan, Huiping; Guo, Miao; Jiang, Lijun
Abstract: The La3-x Yx Ni9.7 Mn0.5 Al0.3 (x = 1, 1.5, 1.75, 2, 2.25, 2.5) alloys were prepared by magnetic suspension induction melting method and annealed at 1273 K for 24 h. The alloys were tested using electrochemical measurements, X-ray diffraction (XRD) and scanning electron microscope with energy-dispersive X-ray diffraction spectroscope (SEM-EDS). With the increase of Y content, the main phase of the alloys changed from Gd2 Co7 phase to Ce2 Ni7 phase, and Ce2 Ni7 phase increased gradually. The maximum discharge capacity of alloys increased from 279.3 mA h/g (x = 1) to 383.8 mA h/g (x = 2.5). The high-rate dischargeabilitiy at the discharge current density of 1200 mA/g increased from 56.98% (x = 1) to 83.76% (x = 2.5). The maximum capacity retention rate first increased from 50.13% (x = 1) to 69.43% (x = 2), and then decreased to 21.35% (x = 2.5). The results showed that the structural stability of the alloys was improved due to the increase of Y content. However, with the increase of Y content, the corrosion, pulverization, and the dissolution of Al element aggravated, which deteriorated the cyclic stability of the alloy electrodes. Highlights: The maximum discharge capacity increased with Y content. The cycle life of alloys first increased and then decreased with increased of Y. The ability of anti-oxidation and anti-pulverization decreased with increased of Y. The Y element in La–Y–Ni alloys can enhance structure stability.